Gene Expression, Biochemical And Functional Analysis Of Stromal Interaction Molecule 1 (Stim1) Silencing In Acute Myeloid Leukemia Cell Lines - Algariri, Eman Salem Saeed (2022)
A stromal interaction molecule (STIM1) was recently discovered to be a critical modulator of cell growth and survival in a variety of cancers. In contrast, the function of STIM1 in AML is still not properly understood. Therefore, the aim of the present study is to investigate the effect of STIM1 on the proliferation and survival of AML cell lines by employing a dicer-substrate siRNA (dsiRNA)-mediated silencing technique performed on two AML cell lines, namely THP-1 and Kasumi-1 cells. The expression profile of critical genes involved in proliferation, survival, and ROS production was analyzed through RTqPCR after STIM1 silencing. The intracellular calcium and ROS levels, cell proliferation, and colony formation were also measured after silencing of STIM1. The study findings revealed that STIM1 mRNA expression was higher in THP-1 cells compared to Kasumi- 1 cells. STIM1 silencing, at the mRNA and protein levels, was achieved in THP-1 cells using 10 nM dsiSTIM1 for 24 hours and 20 nM dsiSTIM1 for 48 hours in Kasumi-1 cells. STIM1 silencing resulted in down-regulation of KRAS, MAPK, C-MYC, Akt, NOX2 and PKC in both AML cells, whereas BAX was up-regulated, and Bcl-2 was down-regulated only in THP-1 cells. Furthermore, STIM1 silencing resulted in a reduction in the intracellular calcium and ROS levels and inhibition of AML cell proliferation and colony formation in both AML cells. In conclusion, the present study suggests that STIM1 might have a crucial role in promoting the proliferation and survival of AML cells